Weaving Hope in Uncertain Times: implementation of the Nation Plan of Prevention of Unintentional Pregnancy in Adolescence during pandemics by covid-19 in Santiago del Estero, Argentina: Weaving Hope in Uncertain Times: implementation of the Nation Plan of Prevention of Unintentional Pregnancy in Adolescence during pandemics by covid-19 in Santiago del Estero, Argentina (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
This article analyses the implementation of a national prevention policy from the experience of advisors of the National Plan for the Prevention of Unintended Pregnancy in Adolescence (Plan ENIA) during the first year of the COVID-19 pandemic in Santiago del Estero, Argentina. From a perspective related to Collective Health articulated with Latin American critical pedagogies, interviews were conducted with ENIA Plan advisors in different cities of the province. The results highlight the transformations produced by the Plan in terms of access to health care, not only with regard to unintended pregnancy, but also to health care in general, despite the precarious working conditions of its advisors. The generation of intersectoral bridges between the education and health systems, facilitated by networks produced by the advisors, was also evident. This made it possible to bring adolescents, an often neglected population, into the health system and to open spaces for reflection on health, sexuality and gender roles. The study highlights the need to identify the limits and scope of these strategies in order to consolidate progress and strengthen precarious links in a province with high levels of poverty and inequality. This would allow for the development of public policies based on democratic paradigms.